2016
DOI: 10.1093/eurheartj/ehw285
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon or radiofrequency ablation for symptomatic paroxysmal atrial fibrillation: reintervention, rehospitalization, and quality-of-life outcomes in the FIRE AND ICE trial

Abstract: AimsThe primary safety and efficacy endpoints of the randomized FIRE AND ICE trial have recently demonstrated non-inferiority of cryoballoon vs. radiofrequency current (RFC) catheter ablation in patients with drug-refractory symptomatic paroxysmal atrial fibrillation (AF). The aim of the current study was to assess outcome parameters that are important for the daily clinical management of patients using key secondary analyses. Specifically, reinterventions, rehospitalizations, and quality-of-life were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
203
1
19

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(232 citation statements)
references
References 15 publications
9
203
1
19
Order By: Relevance
“…In particular, we observed significant interactions for cardioversion and ablation therapy that were related to a reduced symptom burden. It is well known that AF‐related therapy helps to improve symptom burden 12, 13, 14. In a prior observational study, QoL in patients with newly diagnosed AF reached normal values under pharmacologic therapy and cardioversion 15.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, we observed significant interactions for cardioversion and ablation therapy that were related to a reduced symptom burden. It is well known that AF‐related therapy helps to improve symptom burden 12, 13, 14. In a prior observational study, QoL in patients with newly diagnosed AF reached normal values under pharmacologic therapy and cardioversion 15.…”
Section: Discussionmentioning
confidence: 92%
“…It has been shown that the efficacy of this technique is similar to the standard RF-based AF ablation and may be associated with lower hospital readmissions, direct electrical cardioversions and repeated ablations [1,7] . Also the learning curve is much shorter than in the case of RF ablation, which gives a promise for more widespread use of this technique than difficult pointby-point RF ablation [8,9] .…”
Section: Discussionmentioning
confidence: 94%
“…32 In a subgroup analysis of the secondary endpoints, such as rehospitalization, a requirement for cardioversion, and repeat PVI, cryoballoon performance appeared to be a slightly better option. 33 Maan et al 34 did an extensive review of AF ablation complications, including of cryoballoon-associated complications, and reported that the most frequent complication was phrenic nerve palsy, which is specifically more likely to occur when a smaller 23 mm (rather than 28 mm) balloon is used to isolate the right superior PV. [35][36][37] …”
Section: Data On Complications Reported In Published Studiesmentioning
confidence: 99%